Efektivitas Model Eliciting Activitis (Meas) Terhadap Kemampuan Representasi Matematis Siswa MTs - Hosnia; Siti Nur Asmah; Metia Novianti (Kilau Publishing, 2024)
The purpose of this research is to describe and obtain data on the influence of Model-Eliciting Activities (MEAs) on the representational ability of MTs students. This type of research is an experimental study with control and experimental groups by observing the results of pretests and posttests. The research instrument is a mathematical representation ability test. The population of this research consists of all students at MTs Madrasah Miftahul Ulum II Punggur Kecil, with the sample being two eighth-grade classes selected purposively from the seven existing classes. Data analysis was conducted using a two-population mean difference test. The results of the study show that the mathematical representation ability of students who received Model-Eliciting Activities is better than that of students who received conventional teaching. The improvement in the mathematical representation ability of students who received Model-Eliciting Activities in both the upper and lower groups is statistically better than that of students who received conventional teaching.